(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
The integration of artificial intelligence (AI) with augmented reality (AR) and virtual reality (VR) technologies represents a rapidly evolving direction in modern neurorehabilitation. Neurological disorders, including stroke, traumatic brain injury, Parkinson’s disease, and spinal cord injuries, are among the leading causes of long-term disability worldwide and require prolonged, intensive rehabilitation. Conventional rehabilitation approaches are often limited by insufficient personalization, therapist workload, and reduced patient motivation. This article examines the current state of AI-driven AR/VR technologies in neurological rehabilitation, analyzes their clinical effectiveness, identifies key challenges, and discusses future development prospects in accordance with international research trends and evidence-based practice. The study highlights the potential of intelligent immersive technologies to improve functional recovery, enhance patient engagement, and optimize rehabilitation outcomes.